Mapping the Trends and Development of Ethnoscience Research in Science Education: A Bibliometric Analysis (2015–2025) - Ahmad Hardyan Isnaini; Mahrus Mahrus; Muhamad Rizqi Duha Pramudya; Rahma Adinda Putri; Naveed Toofani; Rangga Alif Faresta (Indonesian Journal of Educational Innovation, 2026)
The integration of local wisdom into science education is increasingly recognized for fostering contextual learning; however, a comprehensive mapping of its global development remains limited. This study aims to map the publication trends, knowledge structures, and future trajectories of ethnoscience research over the past decade. A bibliometric analysis was conducted on 849 articles published between 2015 and 2025, sourced from the Dimensions.ai database, and visualized using VOSviewer. The findings reveal a significant publication surge peaking in 2025 (29.1%), with Indonesia driving the research output primarily through teacher education institutions. Co-occurrence analysis identifies four distinct thematic clusters: macro-level curriculum policy, instructional material development, experimental Classroom implementation, and student performance evaluation. The structural evolution of these clusters suggests that ethnoscience is increasingly being adopted as a viable instructional approach. Nevertheless, significant research gaps remain, particularly at the intersection of climate change adaptation and emerging technologies. The implications of this study provide a concrete roadmap for future researchers, highlighting the critical need to integrate ethnoscience with artificial intelligence and global environmental challenges to ensure the sustained relevance of culturally responsive science education.